Novel defatting strategies reduce lipid accumulation in primary human culture models of liver steatosis - Lynda Aoudjehane; Jérémie Gautheron; Wilfried Le Goff; Claire Goumard; Julia Gilaizeau; Chan Sonavine Nget; Eric Savier; Muhammad Atif; Philippe Lesnik; Romain Morichon; Yves Chrétien; Yvon Calmus; et al. (The Company of Biologists, 2020)
Normothermic perfusion provides a means to rescue steatotic liver grafts, including by pharmacological defatting. In this study, we tested the potential of new drug combinations to trigger defatting in three human culture models, primary hepatocytes with induced steatosis, primary hepatocytes isolated from steatotic liver, and precision-cut liver slices (PCLS) of steatotic liver. Forskolin, L-carnitine and a PPARα agonist were all combined with rapamycin, an immunosuppressant that induces autophagy, in a D-FAT cocktail. D-FAT was tested alone or in combination with necrosulfonamide, an inhibitor of mixed lineage kinase domain like pseudokinase involved in necroptosis. Within 24 h, in all three models, D-FAT induced a decrease in triglyceride content by 30%, attributable to an upregulation of genes involved in free fatty acid β-oxidation and autophagy, and a downregulation of those involved in lipogenesis. Defatting was accompanied by a decrease in endoplasmic reticulum stress and in the production of reactive oxygen species. The addition of necrosulfonamide increased the efficacy of defatting by 8%-12% in PCLS, with a trend towards increased autophagy. In conclusion, culture models, notably PCLS, are insightful to design strategies for liver graft rescue. Defatting can be rapidly achieved by combinations of drugs targeting mitochondrial oxidative metabolism, macro-autophagy and lipogenesis.